XÁC ĐỊNH CÁC THAM SỐ CỦA MÔ HÌNH HÀM HIỆP ƯỚC PHƯƠNG SAI DỊ THƯỜNG TRỌNG LỰC Ở VIỆT NAM - Lân, Phạm Hoàng (Vietnam Journal of Earth Sciences, 2005)
The paper presents a method for determining parameters of covariance function of gravity anomalies according to the modified Jordan’s model. Using actual gravimetric data, there are given the values of that parameters for Bouguer anomalies in 10 different areas on Viet Nam’s territory.